The terrorism and the international responsibility - Omran Issa Hamoud Al-Gobury (Journal of Madenat Alelem University College, 2017)
The research in the terrorist phenomenon (concepts and goals) is an issue which dominated the argument and variation. Surely these terrorist concepts still moving in time and place according to national and regional conciliators, in addition comprehensiveness of terrorist operations, all this formed a danger at the whole national society, so the national responsibilities are limited according to national law and jurisprudence which tried to decide the responsibilities of terrorist supporters in any mean and facility. It is important to work hard to combat terrorist and drying its resources , trying hardly to prevent all terrorist operations at all levels, so all concerned in studying the terrorist phenomenon define it as ( the work of horror among the people, hurt them and risk their lives), due to this definition terrorist must be combat and remove all its reasons by planning a near and far strategies to avoid this terrorist phenomenon, in addition activating the strategies and laws prepared by UN and regional organizations which are concerned in this issue. In the recent years the terrorist activities are expanded, so it demands to work hard and taking procedures to prevent all terrorist operations and defeat the terrorist casks everywhere, because the supporter states cause many damages and harms. This work conflicts with national law rules and requires to punishments according to national law rules because they cause many damages and harms which are legally undesired. It is important to prevent these crimes by the execution of all decisions and resolutions of UN concerned in this issue, or any conditions of national law rules for penalties included coercion which incumbent the states to implement as individual or groups to prevent all these terrorist operations.